Comparison of two different container designs and UV-C LED configurations in their drinking water disinfection efficiency - Caduff, Lea; Englert, Alexander; Meierhofer, Regula; Burkhardt, Michael (Frontiers in Water, 2025)
Safe drinking water free of microbial contamination can be obtained by using water treatment technologies, such as UV irradiation, applied at the household level. This study investigated the disinfection efficiency of two different configurations of UV-C LEDs in water containers (domes with five LEDs and a lance containing 40 LEDs), and it assessed their potential for providing effective drinking water treatment options at the household level. Male-specific (MS2) coliphages were used as biodosimeters, and their concentration was measured before and after a defined irradiation time to calculate the log inactivation. The reduction equivalent dose (RED) was calculated using averaged data from published collimated beam experiments. One of the two configurations (domes) achieved a 4-log inactivation in two different containers, even though it consisted of eight times fewer LEDs than the lance: the container with a volume of 11.1 L and a RED of 1,120 J/m2 after an exposure time of 6 h and the container with a volume of 31.1 L and a RED between 735 J/m2 and 1,821 J/m2 after 6–12 h of exposure time. The disinfection efficiency of both configurations could be improved by including a stirring device or flow-through solution to avoid the occurrence of non-irradiated water and a placement of LEDs that avoid the overlapping of UV-C light cones and allow for large light cone formations. It was demonstrated that UV-C LEDs can be combined with ordinary containers in a low-cost, self-built setup and can be applied to treat drinking water.